Fluidized bed photoreactors using composites of titania CVD-coated onto quartz sand as photocatalyst: Assessment of photochemical efficiency - Pozzo, Roberto Luis (2006)
The photochemical efficiency of a fluidized bed (FB) of quartz sand coated with TiO2 by plasma-CVD, was investigated using a fully illuminated, parallel planar photoreactor. The local volumetric rate of photon absorption (LVRPA) of the devicewas obtained by the combined use of experimental measurements and computer modeling of the radiation field. Because of the anisotropy of the FB in the vertical direction, due to particle segregation, and the strong absorption of radiation of the photocatalyst particles across the photoreactor, a two-dimensional modeling (2D) was developed. To accomplish these goals, the relevant specific volumetric optical parameters (namely, the spectral absorption and scattering coefficient) of FBs of the TiO2-coated quartz catalytic composite were used. To take into account said vertical anisotropy of the fluidized bed, a functional dependency between the spectral optical coefficients and bed height was derived in the present work, by assuming a completely segregated FB, and experimentally validated through transmittance measurements. Finally, the evaluation of the photochemical efficiency of the FB in the decomposition of oxalic acid, a well-known model reactant, revealed that this type of devices might outperform the conventional slurry systems, as well as dispense of downstream separation steps